Adenosine receptor activation improves microcirculation in experimental intestinal ischemia/reperfusion - Zhou, Juan; Zimmermann, Katrin; Krieg, Thomas; Soltow, Marieke; Pavlovic, Dragan; Cerny, Vladimir; Lehmann, Christian (Clinical hemorheology and microcirculation, 2015)
Gut ischemia and reperfusion (IR), e.g. in small bowel transplantation or during resuscitation, may result in severe impairment of the intestinal microcirculation. Potential sequelae are mucosal damage, loss of intestinal barrier function, bacterial translocation, systemic inflammation, multiple organ failure and death. We hypothesized a protective role for extracellular adenosine signalling in intestinal IR injury. Using intravital microscopy we investigated the effects of the adenosine receptor (AR) agonist NECA (5'-N-ethyl carboxamide adenosine) on leukocyte-endothelial interactions and capillary perfusion in the intestinal microcirculation following intestinal IR. Six groups of Lewis rats (n = 44) were studied: control, NECA (5'-N-ethyl carboxamide adenosine), IR (30 minutes of intestinal ischemia, 2 hours of reperfusion), IR + NECA, IR + NECA + MRS1754 (A(2B)AR antagonist), IR + NECA + DPCPX (A(1)AR antagonist). All substances were administered i.v. immediately after declamping of the superior mesenteric artery. Intravital microscopy was performed after 2 hours of reperfusion. Following IR we observed a significant increase of leukocyte adhesion in the intestinal submucosal venules and a reduced capillary perfusion within the muscular layers. NECA reduced leukocyte activation and improved capillary perfusion significantly. Administration of A(2B)AR antagonist completely reversed the NECA effect, whereas A(1)AR inhibition only partially abolished the action of NECA. The data support the hypothesis that adenosine signalling is involved in intestinal IR injury. A(2B)AR may be more important than A(1)AR because A(2B)AR inhibition by MRS1754 completely reversed the effect of the adenosine receptor agonist NECA.
Keywords: modely nemocí na zvířatech; střeva; purinergní receptory P1; Male; functional capillary density (FCD); mužské pohlaví; microcirculation; reperfuzní poškození; adenosine receptor; krysa rodu Rattus; Animals; zvířata; Rats, Inbred Lew; intestine; reperfusion; Rats; Disease Models, Animal; ischemia; Reperfusion Injury; mikrocirkulace; potkani inbrední LEW; capillary perfusion; Intestines; Adenosine; Microcirculation; intravital microscopy; leukocyte adhesion; Receptors, Purinergic P1